Artificial sweetener consumption and risks of dementia and stroke. Issue 4 (April 2018) - Castelli, Gregory; Wilson, Stephen A.
Abstract : N/A: Pase MP, Himali JJ, Beiser AS, Aparicio HJ, Satizabal CL, Vasan RS, et al. Sugar‐ and artificially sweetened beverages and the risks of incident stroke and dementia: a prospective cohort study. Stroke . 2017; 48(5):1139–1146.